Effect of salivary gland extract from Ixodes ricinus ticks on the proliferation of Borrelia burgdorferi sensu stricto in vivo - Machácková, Martina; Oborník, Miroslav; Kopecký, Jan (Folia parasitologica, 2006)
Saliva-activated transmission (SAT) of Borrelia burgdorferi sensu stricto was demonstrated using real-time PCR and salivary gland extract (SGE) from partially fed Ixodes ricinus ticks. C3H/HeN mice were injected intradermally with 1.5 x 10(3) spirochetes mixed with 40 microg of SGE per mouse. The control group was inoculated with the same dose of spirochetes without SGE. The accelerating effect of SGE on spirochete proliferation was demonstrated on day 1 post infection, when a 4.2-fold increase in spirochetes was found in the skin and a 10-fold increase in the blood, compared with control mice. The data represent the first direct evidence of a SAT effect of I. ricinus SGE on infection with the Lyme disease agent B. burgdorferi.
Keywords: lymeská nemoc; Borrelia burgdorferi; polymerázová řetězová reakce; klíště; Tissue Extracts; tkáňové extrakty; Mice, Inbred C3H; Lyme Disease; Salivary Glands; myši inbrední C3H; Animals; ženské pohlaví; zvířata; myši; Ixodes; Polymerase Chain Reaction; Mice; Female; slinné žlázy